2014
DOI: 10.1111/pbi.12225
|View full text |Cite
|
Sign up to set email alerts
|

Altered lignin biosynthesis using biotechnology to improve lignocellulosic biofuel feedstocks

Abstract: SummaryLignocellulosic feedstocks can be converted to biofuels, which can conceivably replace a large fraction of fossil fuels currently used for transformation. However, lignin, a prominent constituent of secondary cell walls, is an impediment to the conversion of cell walls to fuel: the recalcitrance problem. Biomass pretreatment for removing lignin is the most expensive step in the production of lignocellulosic biofuels. Even though we have learned a great deal about the biosynthesis of lignin, we do not fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 120 publications
(164 reference statements)
1
52
0
1
Order By: Relevance
“…Figure 1 shows a typical structural model of lignin. Gymnosperms contain almost entirely G unit in lignins; dicotyledonous angiosperms contain G and S units in lignins; and all the G, S, and H units can be found in monocotyledonous lignins [5]. Other units with relatively fewer contents were also identified in the lignin of LCBM, such as ferulates and coumarates [6].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a typical structural model of lignin. Gymnosperms contain almost entirely G unit in lignins; dicotyledonous angiosperms contain G and S units in lignins; and all the G, S, and H units can be found in monocotyledonous lignins [5]. Other units with relatively fewer contents were also identified in the lignin of LCBM, such as ferulates and coumarates [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies using T-DNA insertion mutagenesis and RNA interference technologies showed the knock-out/knock-down of genes involved in lignin biosynthesis resulting in a considerable reduction (10%-50%) of overall lignin content of the transgenic plants [67]. The lignin reduction in plant biomass often comes with a fitness cost, which might compromise the plant's ability to withstand biotic and abiotic stresses.…”
Section: Reducing the Lignin Content/altering The Composition For Easmentioning
confidence: 99%
“…The lignin reduction in plant biomass often comes with a fitness cost, which might compromise the plant's ability to withstand biotic and abiotic stresses. These genetically engineered low lignin plants are often weak and produce lower total biomass due to the lack of lignin deposition in structural cells like xylem, tracheary elements and vessels [67]. Additionally, genetic engineering of lignin can affect related secondary metabolite biosynthesis (flavonoids, coumarins and phenolic compounds), influencing normal plant growth and development [67].…”
Section: Reducing the Lignin Content/altering The Composition For Easmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin, a heterogeneous phenolic polymer comprised of p-hydroxyphenyl (H), guaiacyl (G) and syringyl (S) monomer units, interacts with cell wall polysaccharides to form a complex structure that is resistant to enzymatic breakdown (Boerjan et al 2003). Several greenhouse and field experiments have shown that cell wall saccharification and biofuel yields of switchgrass and other biofuel feedstocks can be significantly improved by manipulating the lignin biosynthetic pathway (Baxter et al 2015;Poovaiah et al 2014). One approach is to reduce the expression of a single gene in the lignin biosynthetic pathway, as demonstrated by switchgrass plants with downregulated caffeic acid O-methyltransferase (COMT), an enzyme primarily involved in S-lignin synthesis.…”
Section: Introductionmentioning
confidence: 99%